Performance Evaluation of Vehicular Ad Hoc Networks Considering Malicious Node Impact on Quality of Services Metrics - Alfarizi, Naufal Faiz; Nuruzzaman, Muhammad Taufiq; Uyun, Shofwatul; Sugiantoro, Bambang; Abdullah, Mohd. Fikri Azli bin (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2025)
Vehicular Ad Hoc Networks (VANETs), a subset of mobile ad hoc networks (MANETs), is essential for enabling communication between vehicles in intelligent transportation systems. However, their dynamic and decentralized nature exposes them to significant security threats, particularly from malicious nodes. Attacks such as black holes and wormholes can severely degrade network performance by causing packet loss and increasing end-to-end delays. This paper aims to evaluate the impact of malicious node behavior on VANET performance using key Quality of Service (QoS) parameters, including throughput, end-to-end delay, jitter, packet delivery ratio (PDR), and packet loss ratio (PLR). The specific objective is to analyze how black hole and wormhole attacks affect communication efficiency in VANET environments. The main contribution of this work lies in the integration of Simulation of Urban Mobility (SUMO) for realistic traffic scenario generation with Network Simulator 3 (NS-3) for detailed network performance evaluation. This approach enables comprehensive simulation of VANET behavior under attack conditions. The findings provide valuable insights into the vulnerabilities of VANETs and form a basis for the design of more robust and secure vehicular communication systems.